BODY LANGUAGE IN EDUCATION - Akramova Kamola Akramovna; G’aybullayeva Mohichehra Narzulla kizi (Western European Studies, 2025)
It is important part of nonverbal communication, body language; it has a very strong effect on learning. It often communicates more than words do; for instance, while sitting or standing, looking at someone straight and making faces and gestures may be regarded as physical movement. It is important in maintaining classroom dynamics, motivating students to learn and developing the teacher-pupil relationships in education. This paper deals with the importance of body language for education, the many ways it could be regarded when it comes to student behavior, cultural diversities, and the successfulness of instruction. It also highlights the challenges related to decoding the nonverbal clues and offers ways for teachers to optimize their use of body language.
Keywords: Silent signals; Assertive posture; De-escalating conflicts